Energy storage system for global maximum power point tracking on central inverter PV plants - Muller, Nicolas; Kouro, Samir; Renaudineau, Hugues; Wheeler, Patrick (2016)
Central inverters are the most common configuration for large-scale photovoltaic systems. Under partial shading or any non¬uniform conditions on the photovoltaic plant, several power maxima may arise. Conventional perturb and observe and other classical maximum power point tracking algorithms are capable of tracking a local maximum, but can not guarantee to operate at the global maximum. A solution to such limitation is to perform a scan of the photovoltaic characteristic periodically in order to ensure operation at the global maximum. However, such a scan generates high output power variations that may not comply with grid codes. In order to overcome this drawback and allow a global scan for maximum power point tracking purposes, this paper proposes a hybrid photovoltaic system with an ultra-capacitor based energy storage system. Simulations are provide to validated the proposed configuration. Results show that the photovoltaic scan allows operation at the global maximum power point, while the ultra-capacitor manage the power transient so that the output fluctuation are kept within reasonable limits.